2009
DOI: 10.1139/b09-030
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive epigenetic memory of ancestral temperature regime inArabidopsis thalianaThis paper is one of a selection of papers published in a Special Issue from the National Research Council of Canada – Plant Biotechnology Institute.

Abstract: Although certain acquired nongenetic (i.e., epigenetic) traits are known to be heritable in plants, little is known currently about whether environmental parameters can induce adaptive epigenetic responses in plants and whether such effects can persist through generations. We used an experimental design based on classical genetics principles to assess whether plants respond to the environmental conditions of their ancestors in an adaptive epigenetic manner. An extensive examination of genetically identical Ara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(57 citation statements)
references
References 39 publications
0
57
0
Order By: Relevance
“…Our data thus extend these observations by demonstrating an enrichment of components of the transcription machinery at promoter regions of primed defense genes, suggesting that an open chromatin configuration provides docking sites for transcription coactivators during priming. Although recent studies suggest a possible transgenerational inheritance of stress memory through epigenetic changes (Whittle et al, 2009;Boyko et al, 2010;Lang-Mladek et al, 2010;Bilichak et al, 2012;Luna et al, 2012), chromatin modifications induced by recurrent environmental challenges were transient, indicating that, as commonly accepted (Ito et al, 2011;Pecinka and Mittelsten Scheid, 2012), disturbed chromatin marks were rapidly restored to prestress chromatin states. All stresses tested induced similar amounts of chromatin modifications, and relative enrichments for H3K9K14ac were kept for 5 d but were not observed after a recovery phase of 7 d after repetitive heat, cold, or salt treatment.…”
Section: Discussionmentioning
confidence: 91%
“…Our data thus extend these observations by demonstrating an enrichment of components of the transcription machinery at promoter regions of primed defense genes, suggesting that an open chromatin configuration provides docking sites for transcription coactivators during priming. Although recent studies suggest a possible transgenerational inheritance of stress memory through epigenetic changes (Whittle et al, 2009;Boyko et al, 2010;Lang-Mladek et al, 2010;Bilichak et al, 2012;Luna et al, 2012), chromatin modifications induced by recurrent environmental challenges were transient, indicating that, as commonly accepted (Ito et al, 2011;Pecinka and Mittelsten Scheid, 2012), disturbed chromatin marks were rapidly restored to prestress chromatin states. All stresses tested induced similar amounts of chromatin modifications, and relative enrichments for H3K9K14ac were kept for 5 d but were not observed after a recovery phase of 7 d after repetitive heat, cold, or salt treatment.…”
Section: Discussionmentioning
confidence: 91%
“…For instance, nitrogen deficiency-induced transgenerational DNA methylation changes in rice, which enhance stress tolerance, could be passed on to the subsequent generations24. Additionally, heat treatment-induced epigenetic memory in the parental and F1 generations of A. thaliana greatly improved the fitness of plants exposed to heat in a later generation (F3)25. In allopolyploid orchids, stable epigenetic effects impacted their adaption to the ecological environment26.…”
Section: Discussionmentioning
confidence: 99%
“…In Sheepshead minnow fish ( Cyprinodon variegatus ), for example, the effects of parental temperature treatment were expressed differently depending on the temperature experienced by juvenile offspring (Salinas and Munch, 2012). In plants, such context-specific expression of inherited environmental influences are widespread; the effects of parental drought (Sultan et al, 2009; González et al, 2017), shade (Galloway and Etterson, 2009; McIntyre and Strauss, 2014), nutrient availability (Latzel et al, 2010, 2014), CO 2 concentration (Lau et al, 2008), salinity (Van Zandt and Mopper, 2004; Vu et al, 2015; Groot et al, 2016; Moriuchi et al, 2016), and temperature (Whittle et al, 2009; Zhang et al, 2012) have all been shown to be expressed differently in alternative offspring environments.…”
Section: Discussionmentioning
confidence: 99%